Is Nigerian Growth Public Spending-Spurred? - OLAYEMI, Ismail Adigun (Asian Journal of Economic Modelling, 2017)
This study, using the Ram framework investigates the effect of government expenditure on the economic growth of Nigeria with a data span of 36 years (1981 to 2016) employing the Autoregressive Distributed Lag (ARDL) Model. It is discovered that government expenditure on human capital development (Education and Health) affects economic growth significantly more especially in the long run; government consumption expenditure and private sector investment have been less significant to growth, while government capital/investment expenditure spurs growth not in the short but in the long run. It is recommended that although government expenditure is important to foster growth, government should focus more on investment expenditure.